Materials and electrical characterization of Er(Si1-xGex)(2-y) films formed on Si1-xGex(001) (x=0-0.3) via rapid thermal annealing - Setiawan, Y. (2012)
We studied erbium germanosilicide films formed on relaxed p-type Si1−xGex(100) (x = 0–0.3) virtual substrates by conventional rapid thermal annealing (RTA) at temperatures of 500–700°C. Two dimensional X-ray diffraction and pole figure measurements revealed that the silicide films formed were epitaxial Er(Si1−xGex)2−y with orientation relationship Er(Si1−xGex)2−y(1100)- [0001]||Si1−xGex(001)[110] or Er(Si1−xGex)2−y(1100)[0001]||Si1−xGex(001)[110]. Schottky barrier height, Φ(Bp), of the Er(Si1−xGex)2−y/p − Si1−xGex(100) contact was found to decrease from 0.79 to 0.62 eV with increasing Ge (from 0 to 30%), implying a slight increase in its barrier height for electrons, Φ(Bneff), from 0.33 to 0.37 eV